Economic Inequality and Covid-19 Death Rates in the First Wave, a Cross-Country Analysis - James B. Davies (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The cross-country relationship between Covid-19 crude mortality rates and previously measured income inequality and poverty in the pandemic's first wave is studied, controlling for other underlying factors, in a sample of 141 countries. An older population, fewer hospital beds, lack of universal BCG (tuberculosis) vaccination, and greater urbanization are associated with higher mortality. The death rate has a consistent strong positive relationship with the Gini coefficient for income. Poverty as measured by the 1.90 per day standard has a small negative association with death rates. The elasticity of Covid-19 deaths with respect to the Gini coefficient, evaluated at sample means, is 0.9. Assuming the observed empirical relationships unchanged, if the Gini coefficient in all countries where it is above the OECD median was instead at that median, 67,000 fewer deaths would have been expected after 150 days of the pandemic - - a reduction of 10%. Shrinking “excess Gini's” down to the G7 median reduces predicted deaths by 88,500, or 14%.
Keywords: I14; I39; 330; Covid-19 pandemic inequality poverty mortality